Device for measurement of biological tissue electric characteristics - Козин, Ю.И.; Леонидов, В.И.; Кравцов, А.В.; Бобнев, Р.А. (Radiotekhnika, 2016)
The possibility is shown to create devices based on the ArduinoUno platform for measurement of temperature and electrical impedance of the affected areas of biological tissue.